Análisis de capacidades de gestión del conocimiento para la competitividad de PYMES en Colombia (2014)
The capabilities of knowledge management for competitiveness of Small and Medium Size Enterprises (SME) in Colombia is analyzed. For this, three hundred twenty one companies were evaluated in relation to organizational analysis, processes and tools of information and communication technology, to manage knowledge. Advances are evident in the processes of knowledge management, but there is slow progress in organizational development and the use of information and communication technology. This study contributes to the academic community and to the small and medium size companies in the country with a baseline of the state of knowledge management, so that they can formulate actions to enhance their competitiveness.